2019
DOI: 10.3390/app9173445
|View full text |Cite
|
Sign up to set email alerts
|

Surface, Volumetric, and Wetting Properties of Oleic, Linoleic, and Linolenic Acids with Regards to Application of Canola Oil in Diesel Engines

Abstract: Oleic, linoleic, and linolenic acids are the main components of canola oil and their physiochemical properties decide on the use of canola oil as fuel for diesel engines. Therefore, the measurements of the surface tension of oleic, linoleic, and linolenic acids being the components of the canola oil, as well as their contact angles on the polytetrafluoroethylene (PTFE), poly(methyl methacrylate) (PMMA), and engine valve, were made. Additionally, the surface tension and contact angle on PTFE, PMMA, and the engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…The droplets are then encapsulated by an additional aqueous solution containing varying ethanol and glycerol concentrations at the second junction with a dimension of 50 μm (Figure b) to form W/O/W double emulsions (see Materials and Methods section). The wetting properties and contact angle for oleic acid and water with surface modified PDMS have been systematically studied and are the basis for the formation of the emulsions in the device presented herein. The distance between the two junctions was extended through incorporating a serpentine channel into the design (100 μm wide, 6.4 cm long).…”
Section: Resultsmentioning
confidence: 99%
“…The droplets are then encapsulated by an additional aqueous solution containing varying ethanol and glycerol concentrations at the second junction with a dimension of 50 μm (Figure b) to form W/O/W double emulsions (see Materials and Methods section). The wetting properties and contact angle for oleic acid and water with surface modified PDMS have been systematically studied and are the basis for the formation of the emulsions in the device presented herein. The distance between the two junctions was extended through incorporating a serpentine channel into the design (100 μm wide, 6.4 cm long).…”
Section: Resultsmentioning
confidence: 99%
“…In this area, research on Liquified Petroleum Gas (LPG) is popular in many countries [15,24,25], as well as biogas [20], natural gas [26,27], Compressed Natural Gas (CNG) [28][29][30] and Liquified Natural Gas (LNG) [31,32]. Interesting studies have been presented on alternative fuels to diesel, as well as mixtures of both, inter alia, [33][34][35][36][37][38][39]. In the wake of this scenario, a more reliable alternative fuel that can be used alone or along with conventional fuels in existing IC engines, with little to no modification, is required [1,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Taking this into account a series of engine tests in static and dynamic conditions, during which the diesel engine was powered with mixtures of canola oil with the addition of n-hexane were made [21][22][23]. Despite the fact that the addition of n-hexane to canola oil decreased the surface tension, slightly changed the density, and significantly decreased the viscosity of the mixtures, the values for diesel fuel were not obtained [24,25]. An analysis of the subject literature showed that the addition of ethanol to the above-mentioned mixtures may bring the physicochemical properties of canola oil closer to diesel fuel.…”
Section: Introductionmentioning
confidence: 99%